Systematic understandings of the subject, subjectivity, society and child subjectivity (Maestros & Pedagogía, 2025)
The article reflects on the systematic understandings of the subject, subjectivity, and society from Michel Foucault's perspective, highlighting how power relations influence the construction of subjectivity. Foucault, rejecting the notion of an objective and universal truth, argues that power is manifested through discourses and practices that shape individuals. According to Foucault, subjectivity is not an inherent essence but a social and discursive construction molded by disciplinary institutions such as education and medicine. These institutions impose norms and categories that normalize behavior and limit individual freedom. The article delves into how disciplinary power and the regulation of sexuality also influence the formation of the subject, emphasizing the interrelation between knowledge, social control, and identity construction. Finally, childhood subjectivity is presented as a process shaped by power structures within the family, school, and society, where children, from an early age, internalize norms and actively engage in self-surveillance, adhering to the expectations imposed by these mechanisms.
Keywords: Subjectivity; power; discourses; Foucault